Application of Spirulina as an innovative ingredient in pasta and bakery products - Nejatian, Mohammad; Yazdi, Amir Pouya Ghandehari; Saberian, Hamed; Bazsefidpar, Nooshin; Karimi, Amin; Soltani, Arash; Assadpour, Elham; Toker, Omer Said; Jafari, Seid Mahdi (ELSEVIER, 2024)
Spirulina (SP) is the commercial name of Arthrospira algae species, especially A. maxima and A. platensis. This microalga has a unique composition of macro/micronutrients and is therefore characterized by an exceptional nutritional value. It contains a high amount of protein with most of the essential amino acids. It is also considered a good source of omega-3 fatty acids. Other nutritional properties of SP include minerals and antioxidant phenolics. In recent years, there has been a great interest in SP incorporation into food formulations to produce functional foods. In this article, the reports that used SP as an innovative ingredient in the formulation of bakery and pasta products were reviewed. The results of the examined studies indicated that the techno-functional characteristics of the products are not negatively affected if the optimum SP level is added to the food formulations. It seems that the most crucial concern of incorporating SP into different cereal-based products is its significant effect on their sensory properties such as odor, taste and overall acceptance. Several studies have investigated methods to overcome this major challenge: such as the use of ethanol-treated SP, encapsulation and application of flavor-improving agents. Using ethanol to remove SP pigments and using SP powder treated with ethanol in the product formulations can improve the sensory properties of the product. Moreover, encapsulation of SP by covering its odor could generally enhance the customer's satisfaction. More studies are still needed to prove the effectiveness of these techniques.
Keywords: Arthrospira spp; Technological properties; Sensory characteristics; Functional foods; Natural additives; Cereals; TYPE-2 DIABETES-MELLITUS; FATTY-ACID-COMPOSITION; INSULIN-RESISTANCE; METABOLIC SYNDROME; NUTRITIVE-VALUE; PLATENSIS; QUALITY; PROTEIN; MICROALGAE; IDENTIFICATION; Food Science & Technology